HIV Tat-Mediated Induction of Monocyte Transmigration Across the Blood–Brain Barrier: Role of Chemokine Receptor CXCR3 - Niu, Fang; Liao, Ke; Hu, Guoku; Moidunny, Shamsudheen; Roy, Sabita; Buch, Shilpa (Frontiers in Cell and Developmental Biology, 2021)
HIV trans-activator of transcription (Tat), one of the cytotoxic proteins secreted from HIV-infected cells, is also known to facilitate chemokine-mediated transmigration of monocytes into the brain leading, in turn, to neuroinflammation and thereby contributing to the development of HIV-associated neurocognitive disorders (HAND). The mechanism(s) underlying HIV Tat-mediated enhancement of monocyte transmigration, however, remain largely unknown. CXC chemokine receptor 3 (CXCR3) that is expressed by the peripheral monocytes is known to play a role in the monocyte influx and accumulation. In the present study, we demonstrate for the first time that exposure of human monocytes to HIV Tat protein resulted in upregulated expression of CXCR3 leading, in turn, to increased monocyte transmigration across the blood–brain barrier (BBB) both in the in vitro and in vivo model systems. This process involved activation of toll-like receptor 4 (TLR4), with downstream phosphorylation and activation of TANK-binding kinase 1 (TBK1), and subsequent phosphorylation and nuclear translocation of interferon regulatory factor 3 (IRF3), ultimately leading to enhanced expression of CXCR3 in human monocytes. These findings imply a novel molecular mechanism underlying HIV Tat-mediated increase of monocyte transmigration across the BBB, while also implicating a novel role of CXCR3-dependent monocyte transmigration in HIV Tat-mediated neuroinflammation.